Peningkatan Literasi Digital untuk Budaya Partisipasi di Media Sosial untuk siswa SMA: Increasing Digital Literacy for Participatory Culture on Social Media for High School Students - Rianto, Puji; Sofia, Nanum; Murtafi’ah, Banatul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Teenagers are one of Indonesia's most significant gadget and social media users and even the world. The use of gadgets by these teenagers has both positive and negative impacts. Some positive impacts of using gadgets on social media include the opportunity to make good friends, enrich their knowledge, obtain information, and improve self-competence. This community service program aimed at building the positive impact of social media among senior high school students, especially to build a participatory culture. The program was conducted in the form of digital literacy training for students at SMA Muhammadiyah 2 Yogyakarta. The training covers knowledge and skills for producing social media content or messages. Before the training, a pre-test was given to the students to check their level of digital literacy to formulate more appropriate training materials. After six meetings, then, the students were asked to complete the post-test to check the impact of the training on them. The results of the tests showed that the digital literacy training for students at SMA Muhammadiyah 2 Yogyakarta was successful. This was shown by the improved scores of the student's digital literacy skills even after the training.